Liberating Women with Islam? The Islamists and Women's Issues in Jordan - Alatiyat, Ibtesam (Totalitarian movements and political religions, 2010)
The question of where Jordanian Islamists stand on women's rights has generated a great deal of attention over the past few years. An analysis of recent shifts in gender relations and hierarchies within the Jordanian Islamic movement (namely the Muslim Brothers and their political wing the Islamic Action Front and the Islamic Centrist Party) reveals that over the past three decades their views on women's rights have shifted towards embracing a much wider and more visible participation of women in the public space and within the movement itself. This suggests that engaging Islamists in political processes helps a great deal in ‘detraditionalizing’ them. However, since 2003, the women's movement, supported by the Jordanian government, has aggressively promoted a CEDAW‐based discourse on rights that has challenged the Islamists to develop a more explicit discourse on women's rights. The new discourse is distinct in being promoted by women as well as men of the movement. This discourse is not entirely consistent with the above‐stated shifts and reveals a rejection of the body of rights suggested by CEDAW. Our analysis of the reaction to the CEDAW‐based discourse on women's rights shows that the Islamists base their opposition to CEDAW on an argument which states that Islam is concerned with justice rather than equality, yet this argument has not been consistently applied across a number of different issue areas, undermining the position of Islamists with regard to women's rights. The overall conclusion of the analysis is that definite change has occurred with regard to the role and status of women in Jordanian society through the activities of the women's movement and efforts to politically engage Islamists on this issue. Yet these changes remain precarious, as the views of Islamist political parties continue to border on traditionalism.